Bukti-Bukti Leksikal Pembeda Bahasa Wanokaka dan Anakalang di Sumba NTT - I Gede Budasi (MABASAN, 2010)
Wanokaka (Wn) and Anakalang (An) languages are two  of the seven languages spoken in Sumba,  East Nusa Tenggara.  Their speakers  live in Central Sumba Regency in East Nusa Tenggara  Province.  Some linguists have considered the two are dialects of Sumba language.  In Budasi’s study (2007 2009), however, both of them were quantitatively proved  as two diffrent languages spoken in the regency. Based on the lexicostatistics analysis and Swadesh’s classification of language, the  relatedness of the two languages was  75,5 %  which means that they belong to language family (They are not in dialects relationship). Both languages were hyphotesized originally from   Proto Wn-An in Sumba Language Group. Based on this hyphothesis, this paper aims at describing qualitatively the the lexical evidences which differ the two  languages. In this  study, the the compartive method was applied. The population of the study were the speakers of the two languages. Three informant samples were selected based on a set of criteria. The instruments of the data gathering were three word lists: Swadesh, Nothofer, and  Holle; and a tape recorder.  Two types of data: secondary and primary,  were collected.  The obtained data  were analysed descriptively and qualitattively. This study concludes that 24.5 %  of the total lexicons identified from the three word lists are  in different forms that differed the two laguages lexically. Thereare two types of findings. The first findings are a number of lexicons which show the forms  of lexical innovation, that is, the forms of cognat sets which show minimum differences in the their phonological patterns; and. The second, is that,  the existance of lexical retentions generated from the Proto Wn-An.  The whole identified evidences  confirmed  the quantitatif data findings mentioned in Budasi’s study (2007 and 2009), that is, the Wn-An are two different languages generated directly from the Proto Wn-An within Sumba language Group.